Communication Strategy of Jawa Pos to Increase the Reading Interest of Youth Through Zetizen Rubric - Muhmmad Nizar Fahmi; Diyah Indiyati; Agus Purbathin Hadi (JCommsci - Journal Of Media and Communication Science, 2019)
The changing period of generation to generation Z makes the existence of old media shifted by new media. Generation Z tends to rely on new technology to access information. Newspapers as the part of the old media can disappear over time. Jawa Pos as one of the newspapers in Indonesia makes a communication strategy to increase the reading interest of the younger generation. The strategy was made through a rubric of young people named Zetizen, previously named Detection. This study aimed to find out Jawa Pos communication strategy in increasing young people's reading interest through the Zetizen rubric. The research was conducted from February to April 2018 at the Java Bos office. The method used is descriptive qualitative method through a case study approach. The results of the study show that the communication strategy made by Jawa Pos is an online strategy and offline strategy through the Zetizen rubric. These two communication strategies are executed by different divisions, Community Division and Page Division. The online strategy that is carried out by the provision of content through social media and websites that are executed by Division Pages. Page Division is also responsible for one part of the offline strategy, which is providing content through the Zetizen rubric. Community Division handles the process of offline engagement through events held. Keywords: communication strategy; Jawa Pos; reading interest; Zetizen